A 15-million-year-long record of phenotypic evolution in the heavily calcified coccolithophore Helicosphaera and its biogeochemical implications - L. Šupraha; L. Šupraha; J. Henderiks; J. Henderiks (Biogeosciences, 2020)
The biogeochemical impact of coccolithophores is defined not only by their overall abundance in the oceans but also by wide ranges in physiological traits such as cell size, degree of calcification and carbon production rates between different species. Species' sensitivity to environmental forcing has been suggested to relate to their cellular PIC : POC (particulate inorganic carbon : particulate organic carbon) ratio and other physiological constraints. Understanding both the short-term and longer-term adaptive strategies of different coccolithophore lineages, and how these in turn shape the biogeochemical role of the group, is therefore crucial for modeling the ongoing changes in the global carbon cycle. Here we present data on the phenotypic evolution of a large and heavily calcified genus Helicosphaera (order Zygodiscales) over the past 15 million years (Myr), at two deep-sea drill sites in the tropical Indian Ocean and temperate South Atlantic. The modern species Helicosphaera carteri, which displays ecophysiological adaptations in modern strains, was used to benchmark the use of its coccolith morphology as a physiological proxy in the fossil record. Our results show that, on the single-genotype level, coccolith morphology has no correlation with growth rates, cell size or PIC and POC production rates in H. carteri. However, significant correlations of coccolith morphometric parameters with cell size and physiological rates do emerge once multiple genotypes or closely related lineages are pooled together. Using this insight, we interpret the phenotypic evolution in Helicosphaera as a global, resource-limitation-driven selection for smaller cells, which appears to be a common adaptive trait among different coccolithophore lineages, from the warm and high-CO2 world of the middle Miocene to the cooler and low-CO2 conditions of the Pleistocene. However, despite a significant decrease in mean coccolith size and cell size, Helicosphaera kept a relatively stable PIC : POC ratio (as inferred from the coccolith aspect ratio) and thus highly conservative biogeochemical output on the cellular level. We argue that this supports its status as an obligate calcifier, like other large and heavily calcified genera such as Calcidiscus and Coccolithus, and that other adaptive strategies, beyond size adaptation, must support the persistent, albeit less abundant, occurrence of these taxa. This is in stark contrast with the ancestral lineage of Emiliania and Gephyrocapsa, which not only decreased in mean size but also displayed much higher phenotypic plasticity in their degree of calcification while becoming globally more dominant in plankton communities.